آيات الحدود والكفارات من خلال سورة المائدة –دراسة موضوعية- - كشي, عفاف (University of Eloued جامعة الوادي, 2017)
الملخص:. إن الحكمة من الحدود والكفارات هي زجر الناس وردعهم وتخويفهم حتى لا يقعوا في المنكرات والمعاصي، كالقتل والسرقة مثلا ، فالعقوبة في الإسلام والقوانين الإسلامية كلها حق وعدل، لإصلاح الجناة وزجر المجرمين وردعهم، والعقوبة تتفاوت بتفاوت الجريمة ومقدار خطرها، وإخلالها بأمن المجتمع وراحتهم، فإذا كانت عقوبة اللصوص السارقين قطع اليد لأن جريمتهم شخصية خاصة، فإن عقوبة المحاربين قطاع الطرق أشد و أنكى، فهي إما النفي من الأرض أو قطع اليد والرجل من خلاف، أو القتل والصلب، أو القتل فقط لأن جريمتهم تهدد أمن المجتمع برمته، وتنشر الذعر والإرهاب في جميع الأماكن. واحتوت هذه الدراسة التي سلكت المنهج الموضوعي في العمل وأجابت عن الإشكالية الرئيسية، على مقدمة وفصل تمهيدي خاص بالسورة الكريمة وفصلين وخاتمة، ففي الفصل التمهيدي تناولت التعريف بالسورة الكريمة اسمها وفضلها ومحورها وعدد آياتها ومكيّها ومدنيّها وترتيبها وأغراضها ومقاصدها وأما الفصل الأول فكان بعنوان الحدود وفيه نوعان حد الحرابة والسرقة، والفصل الثاني بعنوان الكفارات واشتمل على كفارة اليمين وكفارة الصيّد، ثم الخاتمة التي توصلت فيها إلى مجموعة من النتائج نذكر منها: شمول الشريعة وكمالها، الذي غطى جميع مناحي الحياة وعالج الأحداث والنّوازل على مرّ العصور، وكرّ الدهور، و ضرورة تطبيق الحدود و الكفارات، لردع الناس وتخويفهم حتى لا يقعوا في المنكرات و المعاصي. وفي تقديم السارق على السارقة، والزانية على الزاني فيه عبرة، لأن السرقة تكون من الرجل أجرأ، والزنا يكون على المرأة أقبح وأشنع، ويدور محور السورة حول التشريع لإقامة مجتمع مسلم يستمد أمره من الله، سورة مهمة لورود الأحكام التشرعية فيها وقصص للعبرة والعظة، وذكرت فيها أهم التوصيات المتمثلة في: احترام عهد الله وميثاقه، وتعظيم ذات الله وجلاله، فهي تبعد عن كل مظاهر الإخلال بهيبة الله وقدسيته، والحرص على تطبيق القوانين في الشريعة الإسلامية حتى لا يعم الخوف واللاطمأنينة بين المجتمعات. ABSTRACT: The punishment in Islam and Islamic law is all right and right, to reform the perpetrators and to deny and deter criminals, and the punishment varies with the crime and the amount of danger, and the violation of the security and welfare of the community, if they The punishment of robber thieves is to cut off the hand because their crime is a personal figure. The punishment of the bandits is more severe and selfish. They are either exile from the land or cutting off the hand and the man from disagreement or killing and steel or killing only because their crime threatens the security of the entire society. the places.    This study, which took the substantive approach in the work and answered the main problem, contains a preface and a preliminary chapter on the Gemara, two chapters and an end. In the introductory chapter, the definition of the Holy Qur'an concerned its name, its virtue, its axis, the number of its verses, its meanings, its civilians, its order, its purposes and purposes. And the second chapter entitled Kifarat and included the expiation of the right and the fishing empire, and then the conclusion, which reached a range of results, including: the inclusion of the law and its perfection, which covered all walks of life and treatment of events and castles on the And the need to apply the limits and infidels, to deter people and intimidate them so as not to fall into evil and sin. And the introduction of the thief on the prostitute, and the adulteress on the adulteress therein is a lesson, because the theft is from the boldest man, and adultery is on the woman uglier and ruthless, and revolves the axis of the Sura on the legislation to establish a Muslim community derives its command from God, an important surah for the legislative provisions and stories of speech and sermon, The most important recommendations are: Respect for the covenant of God and His Charter, and to maximize the same God and His Majesty, it is far from all manifestations of violation of God's sanctity and sanctity, and keen on the application of laws in Islamic law so as not to fear and insecurity among communities.
مذكرة ماستر تخصص علوم القرآن
Keywords: الحدود – الكفارات – حد الحرابة – حد السرقة – كفارة اليمين – كفارة الصيّد; Borders - Kefarat - the limit of the war - the limit of theft - the expiation of the right -the expiation of fishing.